A solar cell for maximizing voltage up to the level difference of two photocatalysts: optimization and clarification of the electron pathway. Issue 32 (5th April 2017) - Yoshiba, Mao; Ogura, Yuta; Tamba, Masayuki; Kojima, Takashi; Izumi, Yasuo
Abstract : Light irradiation from the rear side of the photoelectrodes suppresses the electron diffusion overpotential and leakage current resulting in 1.91 V per cell. Abstract : Fuel cells (FCs) and solar cells (SCs) are indispensable devices for a hydrogen energy society. The voltages obtained are less than 1 V per cell for most FCs and SCs. Herein, we use a recently developed SC comprising two photocatalysts. In principle, both TiO2 and BiOCl are photo-excited, and the energy difference between the conduction band (CB) minimum of TiO2 for excited electrons (−0.11 V) and the valence band (VB) maximum of BiOCl for holes (2.64 V) can provide a theoretical electromotive force of 2.75 V. This SC converts light energy into an electromotive force corresponding to the level difference of the two photocatalysts permanently mediated by the redox of water/O2 . The diffusion overpotential of electrons in the photocatalysts (0.23–0.41 V) and the leakage current (0.38 V) are experimentally evaluated. The contact between the TiO2 film and ITO layer is improved by the better dispersion of the TiO2 suspension at a lower pH than that of the isoelectric point. Cyclic voltammetry data suggest the formation of O/Cl vacancy sites during the SC tests and the superiority of the rear orientation of the BiOCl photocatalyst on the cathode and effective photo-oxidation of water over TiO2, whereas impedance measurements suggest a smaller impedance for the tight and uniform TiO2 film in comparison to the porous BiOCl film. Thus, in the optimized configuration of the electrodes (irradiation from the other side of the photocatalyst), the leakage current and the diffusion overpotential in the catalyst layers are effectively suppressed to realize an open-circuit voltage of 1.91 V and cell output of 55.8 µW per 1.3 cm 2 .